Gold Electrocatalysis: Enhanced Methanol Electro‐Oxidation Activity of Nanoclustered Gold (Small 27/2021). Issue 27 (8th July 2021) - Yadav, Anupam; Li, Yejun; Liao, Ting‐Wei; Hu, Kuo‐Juei; Scheerder, Jeroen E.; Safonova, Olga V.; Höltzl, Tibor; Janssens, Ewald; Grandjean, Didier; Lievens, Peter
Abstract : In article number 2004541, Anupam Yadav, Didier Grandjean, Peter Lievens, and co‐workers uncover the origin of the catalytic activity of 3 nm gold clusters by thorough experimental and computational characterization of their properties. Faceted geometries demonstrate significantly enhanced methanol electro‐oxidation activity because of exposed undercoordinated gold atoms on their surface. Vertices and edges are the most active sites because of their favorable CO and OH adsorption energies.